Legal Protection for Medical Personnel in Health Centers based on Law No. 17 of 2023 concerning Health - Dewi Maya Sartika Simangunsong; Irsyam Risdwati; Redyanto Sidi (Journal Evidence Of Law, 2026)
Legal protection for medical personnel in health centers is a very important issue considering the strategic role they play in providing health services to the community. Medical personnel at health centers, both doctors, nurses, and other health workers, often face legal risks in carrying out their duties, whether related to negligence, malpractice, or demands from patients or third parties. Based on this, legal protection for medical personnel needs to be clearly regulated to ensure the sustainability of safe and guaranteed health services. Law No. 17 of 2023 is here to provide a guarantee of better legal protection for medical personnel, especially in the first level of health facilities of Puskesmas. Law No. 17 of 2023 provides a stronger legal basis for medical personnel by affirming their rights in carrying out their profession. One of the important aspects of this law is the existence of rules that ensure that medical personnel will not be punished criminally or civilly as long as the medical actions carried out are in accordance with applicable professional standards and medical ethics. The law also provides for a fairer dispute resolution mechanism, providing opportunities for medical personnel to defend themselves in cases that could potentially harm them, as well as ensuring adequate legal assistance. The importance of this legal protection not only provides a sense of security for medical personnel, but also ensures the quality of health services provided to the community. With clear regulations, medical personnel at Puskesmas can focus more on carrying out their duties without worrying about legal repercussions that can arise due to accidental mistakes. Through Law No. 17 of 2023, it is hoped that a better, fair, and professional health service system will be created, which in turn can increase public trust in health services at Puskesmas.